Introduction — a roundtable on The Woman of Colour (1808) : pedagogic and critical approaches (Roundtable) - Sinanan, Kerry (2021)
The Woman of Colour (1808), an epistolary novel by an anonymous author, remained out of print until 2008 when an authoritative, detailed new edition by Lyndon J. Dominique was published with Broadview. Featuring Olivia Fairfield, the daughter of an enslaved woman and her white “master,” the novel takes the reader from Jamaica to England. Olivia is sent to marry her white cousin Augustus Merton to whom she will be-queath £60,000 in return for being protected and assured of her freedom. As the daughter of an enslaved woman, remaining in Jamaica would be precarious, and, during her time in Eng-land, Olivia gains full independence and the wealth that enables her to return to Jamaica a free person. The plot is structured as a packet of letters that, like its antecedent Samuel Rich-ardson’s Pamela (1740), has been published by a fictional editor. Unlike Pamela, The Woman of Colour contains no editorial “preface.” Instead we have a concluding dialogue in which the fictional editor tells “a friend” that the purpose of the novel is to show how “virtue, like Olivia Fairfield’s, may truly be said to be its own reward.”1 And so The Woman of Col-our explicitly resituates eighteenth-century female virtue in an independent, legally unmar-ried woman—a woman of color, who leaves England for her home in Jamaica to pursue a better life. While the novel remains in many ways trapped within the plot conventions and gendered norms of the Romantic period, it simultaneously rejects them and offers trajectories of emancipation that unsettle gender, race, and nation. This double movement in the novel unsettles white hierarchies of moral superiority and liberal ideals exposing them to be less immutable than they appear.